The role of knowledge management in virtual learning environments: a systematic review - Wahdan, Ahlam (2021)
The main objective of this systematic review is to analyse the up-to-date knowledge management in virtual learning environments studies. In that, 94 research articles ranged between 2005 and 2020 were critically analysed. Subsequently, the researchers integrated the findings to display the output with one result. Various countries hosted the studies; however, China, Iran, and European countries were among the pioneers. Besides highlighting the e-learning, the role of knowledge management processes (KMPs) in virtual learning environments (VLEs) was emphasised by the systematic review. Moreover, it described the successful integration of KM in LMS within the VLE. It also realised the benefits of this integration on e-learning elements: the instructors, the learners, and the organisation. Moreover, knowledge creation is found to be the most adopted KMP in LMS. The findings revealed that the KM significantly contributed to e-learning to create a different and distinct education method leading to a Renaissance in the modern age.